Lipopolysaccharide tolerance in human primary monocytes and polarized macrophages - Li, Hui; Breedijk, Annette; Dietrich, Nadine; Nitschke, Katja; Jarczyk, Jonas; Nuhn, Philipp; Krämer, Bernhard; Yard, Benito A.; Leipe, Jan; Hauske, Sibylle J. (International journal of molecular sciences, 2023)
Innate immune memory allows macrophages to adequately respond to pathogens to which they have been pre-exposed. To what extent different pattern recognition receptors, cytokines and resolution signals influence innate immune memory needs further elucidation. The present study assessed whether lipopolysaccharide (LPS) tolerance in monocytes and macrophages is affected by these factors. Human CD14+ cells were isolated from peripheral blood, stimulated by LPS and re-stimulated after 3 days of resting. Hereafter, immune-responsive gene 1 (IRG-1), heme oxygenase 1 (HO-1), tumor necrosis factor α (TNF-α) and interleukin 6 (IL-6) expression were assessed. Our study revealed the following findings: (1) While pre-stimulation with the Toll-like receptor 4 ligand LPS inhibits the induction of IRG-1, TNF-α and IL-6 expression, pre-stimulation with TLR 1/2 ligands only affects cytokine production but not IRG-1 expression upon subsequent TLR4 engagement. (2) Prior TNF-α stimulation does not affect LPS tolerance but rather increases LPS-mediated cytokine expression. (3) Dimethyl itaconate (DMI) inhibits the expression of IRG-1 in a dose-dependent manner but does not affect TNF-α or IL-6 expression. (4) Docosahexaenoic acid (DHA) partly inhibits IRG-1 expression in monocytes but not in M(IFNγ) and M(IL-4) polarized macrophages. LPS tolerance is not affected in these cells by DHA. The data presented in this study partly corroborate and extend previous findings on innate immune memory and warrant further studies on LPS tolerance to gain a better understanding of innate immune memory at the molecular level.